Oxaloacetate induces apoptosis in HepG2 cells via inhibition of glycolysis. (13th March 2018) - Kuang, Ye; Han, Xiaoyun; Xu, Mu; Yang, Qing
Abstract: Most cancer cells perform glycolysis despite having sufficient oxygen. The specific metabolic pathways of cancer cells have become the focus of cancer treatment. Recently, accumulating evidence indicates oxidative phosphorylation (OXPHOS) and glycolysis can be regulated with each other. Thus, we suggest that the glycolysis of cancer cells is inhibited by restoring or improving OXPHOS in cancer cells. In our study, we found that oxaloacetate (OA) induced apoptosis in HepG2 cells in vivo and in vitro. Meanwhile, we found that OA induced a decrease in the energy metabolism of HepG2 cells. Further results showed that the expression and activity of glycolytic enzymes were decreased with OA treatment. Conversely, the expression and activity of enzymes involved in the TCA cycle and OXPHOS were increased with OA treatment. The results indicate that OA can inhibit glycolysis through enhancement of OXPHOS. In addition, OA‐mediated suppression of HIF1α, p‐Akt, and c‐myc led to a decrease in glycolysis level. Therefore, OA has the potential to be a novel anticancer drug. Abstract : Oxaloacetate induces apoptosis of HepG2 cells via inhibition of glycolysis in vivo and in vitro. OA inhibits glycolysis via enhancement of OXPHOS in HepG2 cells. OA inhibits glycolysis‐related enzyme expression by suppression of the Akt/HIF pathway in HepG2 cells.